Intercropping lettuce and radish as strategy for efficient water use: determination of water demand and crop coefficient - Menezes, Cláudia Salim Lozano; Rezende, Roberto; Wenneck, Gustavo Soares; Saath, Reni; Terassi, Daniele de Souza; Freitas, Paulo Sérgio Lourenço de; Gonçalves, Antônio Carlos Andrade; Andrean, André Felipe Barion Alves (Comunicata Scientiae, 2024)
Determining the need for water, as well as crop coefficients, is essential information for the management of irrigation and consequently efficiency in the use of water resources. The study aimed to determine the evapotranspiration and the culture coefficients of lettuce and radish in a monoculture system and consortium in a protected environment. The lettuce cultivar used was Vanda and for radish hybrid 19 was used. The reference evapotranspiration was estimated by the Penman-Monteith method using data from the automatic weather station and the evapotranspiration of the cultures was determined by the direct method using lysimeters of constant water table. The water demand for lettuce and radish in the intercropping system was 170 mm, being less than the lettuce monoculture which was 190 mm and higher than the radish monoculture which was 121 mm. The recommended average values of culture coefficient for conditions were 0.96, 1.85, and 1.50 for lettuce and 0.85, 1.28, and 1.10 for the radish in the initial, intermediate and final stages, respectively. The intercropped cultivation showed lower water consumption than the lettuce monoculture. The coefficient values of lettuce and radish in a monoculture system were higher than the standard values recommended by FAO, emphasizing the importance of conducting regional studies.